TRADISI PEMAKAIAN IMAMAH PADA MASYARAKAT KETURUNAN ARAB HADRAMI DI CONDET - Sahal, Hasan; Priyoyudanto, Febri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Condet area in East Jakarta has long been associated with the image of being a residential center for people of Arab descent, particularly those originating from the Hadramaut region of Yemen. Since the late 1990s, the population of this community has continued to grow rapidly. One of the most distinctive visual characteristics of the people in this area is their custom of wearing the imamah or turban. For them, the imamah is not merely a traditional garment inherited from their ancestors, but also carries profound religious significance as an expression of obedience in practicing the Sunnah of the Prophet Muhammad ﷺ.Using a literature review approach that draws upon various historical, religious, and socio-cultural sources, this article examines in greater depth the function and meaning behind the tradition of wearing the imamah. The findings reveal that the use of the imamah in Condet is driven by three primary dimensions. First is the religious dimension, namely the practice of the Sunnah. Second is the social dimension, in which the imamah often serves as a symbol of a person's status or scholarly authority, particularly among Islamic scholars (ulama) and habaib. Third, it functions as an affirmation of ethnic identity, helping preserve Hadrami cultural roots amid the diversity of Betawi society.Furthermore, differences in the color, size, and style of wrapping the *imamah* also represent the social and religious stratification within the community itself. Through this article, it is hoped that it will serve as a foundation for further field research, particularly studies concerning the dynamics of religious and ethnic identity among Arab-Yemeni descendant communities in Indonesia.